Clonal evolution of high‐grade serous ovarian carcinoma from primary to recurrent disease. Issue 4 (29th November 2012) - Castellarin, Mauro; Milne, Katy; Zeng, Thomas; Tse, Kane; Mayo, Michael; Zhao, Yongjun; Webb, John R; Watson, Peter H; Nelson, Brad H; Holt, Robert A
Abstract High‐grade serous carcinoma (HGSC) is the most common and fatal form of ovarian cancer. While most tumours are highly sensitive to cytoreductive surgery and platinum‐ and taxane‐based chemotherapy, the majority of patients experience recurrence of treatment‐resistant tumours. The clonal origin and mutational adaptations associated with recurrent disease are poorly understood. We performed whole exome sequencing on tumour cells harvested from ascites at three time points (primary, first recurrence, and second recurrence) for three HGSC patients receiving standard treatment. Somatic point mutations and small insertions and deletions were identified by comparison to constitutional DNA. The clonal structure and evolution of tumours were inferred from patterns of mutant allele frequencies. TP53 mutations were predominant in all patients at all time points, consistent with the known founder role of this gene. Tumours from all three patients also harboured mutations associated with cell cycle checkpoint function and Golgi vesicle trafficking. There was convergence of germline and somatic variants within the DNA repair, ECM, cell cycle control, and Golgi vesicle pathways. The vast majority of somatic variants found in recurrent tumours were present in primary tumours. Our findings highlight both known and novel pathways that are commonly mutated in HGSC. Moreover, they provide the first evidence at single nucleotide resolution that recurrent HGSC arises from multiple clones present in the primary tumour with negligible accumulation of new mutations during standard treatment.